(untitled) (Global Journal of Human-Social Science, 2019)
The ceiling placed on age by government and non-governmental agencies when it comes to employment opportunities in Nigeria, which is usually between 20 and 30 years, has made a lot of applicants outsiders, bracketing them out of consideration in the job selection process, thereby pushing them to have their ages falsely declared in court. The problem is even more prominent in Nigeria where applicants can take up to a decade or more looking for jobs, by which time they get older. For example, in a 2016/2017 recruitment exercise by the Nigerian Police, a candidate applying for the post of a Cadet Assistant Superintendent of Police must be between 23 and 28 years of age. Also, in an advert by Fidelity Bank Plc in 2015 for jobs, one of its key requirements was: an applicant must be between 20 and 28 years. But the Nigerian Constitution Section 42 (2) says no Nigerian shall be deprived of any opportunity based on circumstances of birth. Age is a circumstance of birth. Discrimination on the level of age has forced many applicants to go to court and have their ages falsely declared in order to qualify for jobs advertised, which amounts to perjury -a crime punishable by the Nigerian state itself. Here then lies a social problem for research. This is a qualitative research which used key informant interview in gathering data from two selected organizations in Calabar metropolis. The work sought to ascertain whether there is a relationship between age limit placed by employers and age declaration scam committed by applicants. The paper concluded that all men are created equal and there must be no discrimination whatsoever. Government as custodians of the Constitution should stop the discrimination; they should enact laws against any discriminating employers -were the recommendations made, among others.